Peran Teknologi Dalam Literasi Sains Siswa - Puput Aprilia Eka Sari; Sefti Eka Inggritiya; Moch. Dimas Reza; Rizal Wijayanto; I Ketut Mahardika; Singgih Bektiarso (Jurnal Ilmiah Wahana Pendidikan, 2023)
Linguistically, technology comes from the Greek, namely tekhnologia which is a combination of "techne" and "logos". Tehcne means art or skill while logos means science of study. In the Big Indonesian Dictionary, technology is all means to provide goods needed for the survival and comfort of human life. According to UNESCO "The United Nations Educational, Scientific and Cultural Organization", literacy is a set of real skills, especially skills in reading and writing that are independent of the context in which these skills are acquired and who acquires them. According to Alo Liliweri in the book Philosophy of Science (2022), science is a collection of knowledge and the process of developing knowledge itself. In science, the most core process is to produce a testable explanation, along with its methods and approaches. The role of technology in students' scientific literacy, in other words, is a means with the aim of making it easier for students to improve writing, reading and understanding science knowledge in education.